Estrategias de marketing en FALUVID (aluminio y vidrio) en la ciudad de Babahoyo. - Cornejo Barco, Lilot Denisse (2024)
In the current business context, the Faluvid company, specialized in aluminum and glass products in the city of Babahoyo, faces significant challenges related to the lack of online presence and an effective marketing strategy. The overall objective of this study is to evaluate marketing tactics to attract customers in Faluvid, focusing on a detailed analysis of local competition, and the implementation of effective marketing strategies. The methodology used is based on an analytical approach that uses techniques such as interviews, direct observation and SWOT analysis. The results reveal areas for improvement, highlighting the need to improve the visual impact and message clarity in advertising, as well as diversify online presence and optimize advertising placement. Identified strengths, such as product quality and personalized attention, align with differentiation in the market, while opportunities, such as leveraging digital platforms, highlight the importance of adaptability. In conclusion, the recommendations for implementing marketing strategies based on the findings will position Faluvid as a leader in the aluminum and glass sector, ensuring its continued growth and its ability to meet the changing demands of the local market.